2019
DOI: 10.21833/ijaas.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of earnings management in determining firm value: An emerging economy perspective

Abstract: Resource allocation decisions by investors are made on the basis of information provided by firm management. The reports providing information are prepared with the help of international financial reporting standards (IFRS) which provide a great deal of discretion to the management. Management, on the basis of this discretion, manipulates the financial information particularly earnings of firm termed as earnings management which has important implications for firm future. This earnings management can be accrua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 39 publications
3
22
2
Order By: Relevance
“…On the other hand, it is opportunistic if directors use their discretion for maximizing their utility. Efficient earnings management adds value to a firm, whereas opportunistic earnings management worsens corporate image (Subramanyam 1996;Abbas and Ayub 2019). So far, a lot of research has been done on the impact of earnings management on companies' financial performance, which has led to different results.…”
Section: Earnings Management and Corporate Performancementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it is opportunistic if directors use their discretion for maximizing their utility. Efficient earnings management adds value to a firm, whereas opportunistic earnings management worsens corporate image (Subramanyam 1996;Abbas and Ayub 2019). So far, a lot of research has been done on the impact of earnings management on companies' financial performance, which has led to different results.…”
Section: Earnings Management and Corporate Performancementioning
confidence: 99%
“…On the other hand, the results of many research have shown that profit management leads to the improved financial condition of companies (Sayari and Omri 2017;Khuong et al 2019;Abbas and Ayub 2019;Mostafa 2020;Zhang and Ayisi 2020;Nobakht and Acar 2021). For example, Sayari and Omri (2017) saw a positive relationship between discretionary accruals and Tunisian firms' stocks, indicating that discretionary accruals allow Tunisian investors to construct their stocks portfolios optimally.…”
Section: Earnings Management and Corporate Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the reported earnings can convey information on economic earnings (Dye & Verrecchia, 1995;Laínez & Callao, 1999). Abbas and Ayub (2019) demonstrated that management, on the basis of this discretion, can manipulate the financial information. A reduction in discretion is predicted to lessen a manager's ability to communicate with shareholders (Healy & Wahlen, 1999).…”
Section: Characteristics Of Accounting Rulesmentioning
confidence: 99%
“…Managers are assumed to opportunistically increase prior-year's reported earnings through the choice of accounting methods that provide alternatives to recognition and measurement of financial statements' items. This in turn works in favour of the managers' intended outcome to meet or beat analysts' prediction of earnings in affecting firm equity value (Dakhlallh, Rashid, Wan Abdullah & Qawazeh 2020;Abbas & Ayub 2019).…”
Section: Literature Review and Hypotheses Development Earnings Management Executive Remuneration And Firm Equity Valuementioning
confidence: 99%